(untitled) (Journal of Educational Sciences, 2018)
This article discusses the methodological techniques for analyzing the archetype «house» in the novels of G. Belger. The writer’s works are considered in the aspect of ideological and substantive strengthening of interethnic harmony and tolerance of the peoples of Kazakhstan. The study of archetypes in literary works can reveal not only similarities, but also differences in the linguistic pictures of the world. Understanding these properties is the key to successful intercultural cooperation, the result of which is the peace and well-being of the peoples of our country. Kazakhstan is a Eurasian country, a bridge between cultural and political-economic spaces that are heterogeneous in nature. In order for the model of a new society to take place, it is necessary to understand and accept the achievements of all cultures that are part of our country. In this process, it is impossible to overestimate the role of Kazakh literature, which genetically goes back to the traditions of different eras, to the experience of world literature, to universal human values. The methodical system for analyzing the archetype of the house in the novels of G. Belger is based on the use of various effective methods of interactive, heuristic learning and means of forming critical thinking, in their total contributing to the development of students as full subjects of the cognitive process, which is necessary for their successful professional activities as teachers of Russian and literature. The study of the «house» archetype contributed to the further literary development of students, since they had formed a deep understanding of various aspects of the skill of G. Belger. Formation of ideas about the archetype as a universal category among students aroused their interest in philosophy, cultural studies and psychology. Key words: G. Belger, the novel «The Wanderer’s House», the novel «Tuyuk Su», the archetype «house», tolerance, methodical technique, educational analysis.